2003
DOI: 10.1016/s0029-7844(02)02336-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal evisceration long after vaginal hysterectomy

Abstract: Vaginal evisceration can be treated by a transvaginal surgical approach. Factors such as the medical condition of the patient and the viability of the herniated viscus should dictate the optimal approach in each case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
0
16
0
3
Order By: Relevance
“…Our patient had several of these risk factors including: postmenopausal state, multiparity, constipation, vaginal atrophy and the presence of an enterocele. Case reports have shown that the time of onset of the VE is variable and may range from weeks to years after surgery [7][8][9][10][11][12][13]. The trigger event for VE is usually trauma or early coitus in premenopausal patients, while it happens spontaneously or with increased intra-abdominal pressure in postmenopausal patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had several of these risk factors including: postmenopausal state, multiparity, constipation, vaginal atrophy and the presence of an enterocele. Case reports have shown that the time of onset of the VE is variable and may range from weeks to years after surgery [7][8][9][10][11][12][13]. The trigger event for VE is usually trauma or early coitus in premenopausal patients, while it happens spontaneously or with increased intra-abdominal pressure in postmenopausal patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…L'éviscération est alors déclenchée par une élévation de la pression intra-abdominale (constipation, toux). D'autres facteurs favorisants sont rapportés comme un lâchage de suture, un hématome ou un abcès du site opératoire, la reprise des rapports sexuels avant la cicatrisation vaginale, l'âge avancé de la patiente et son statut hormonal, un antécédent de radiothérapie pelvienne, la prise chronique de corticoïdes, les traumatismes (intromission d'objets, viol) [3]. Notre observation associe plusieurs de ces facteurs de risque et la rupture de l'entérocèle était secondaire à l'évolution d'ulcération sur une muqueuse vaginale ischémique, conséquence de l'âge, du statut hormonal, de la corticothérapie générale chez une patiente ayant pour anté-cédent une hystérectomie vaginale.…”
Section: Discussionunclassified
“…Quel que soit le méca-nisme de l'EV, les patientes se présentent avec une douleur abdominale ou vaginale, une sensation de masse vaginale, un saignement vaginal et parfois, comme dans notre observation, une issue franche transvaginale de tissu digestif [6]. Si l'iléon terminal est l'élément digestif le plus fréquemment éviscéré, d'autres organes peuvent être mis en cause : épi-ploon, colon sigmoïde, annexes [3].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The patient should be placed in the Trendelenburg position and treated empirically with broad-spectrum antibiotics to cover gastrointestinal flora (1). Although bowel viability is best evaluated in the operating room, ED examination of bowel may include descriptions of color such as erythema or duskiness, edema, signs of active peristalsis, or even palpation of mesenteric pulses (9). Suspected viability of exposed bowel and associated peritoneal signs influence decision-making for surgical approach, usually managed from a transvaginal, abdominal, or combined approach.…”
Section: Subtle Vaginal Evisceration E127mentioning
confidence: 99%